Opening Up of Editorial Activities at Chemistry Journals. What Does Editorship Mean and What Does It Involve? - Noel, Marianne (Frontiers in Research Metrics and Analytics, 2022)
The article unpacks the publishing practices and focuses on the curating work carried out by the editors of chemistry journals. Based on a qualitative analysis of multiple sources in two publishing houses, it first shows that the role of editor-in-chief covers a wide range of realities and is far from being limited to that of a gatekeeper (the most common metaphor in the literature). In journals that are part of the Nature Research portfolio, in-house editors, who are no longer active scientists, work full time for the journals. The article describes the professional trajectories and skills required to join the publishing house. Interviews highlight collective identity-based actions, attention to the growth and the flow of manuscripts, but also specific epistemic properties of outputs in chemistry. Besides tasks that editors outline “as really the same as they were hundred years ago”, as they spend most of their time handling manuscripts and providing quality assurance, they also travel to conferences to support journals and encourage submissions, visit labs where researchers pitch their work or ask questions about journals, and “educate the actors themselves” about new fields. In both cases studied, the publishing houses partner with institutions to offer events (ACS on Campus programme, Nature masterclass) that a university or department can freely host or buy, where editors organize workshops on all aspects of manuscript preparation. Second, publishing houses, whether non-for-profit or commercial, have embraced a catalogue logic, where the journals are not necessarily in competition and have an assumed place and hierarchy. At Nature Research, editors-in-chief head business units inscribed in the company’s organization. Despite standardized processes imposed by the procedural chain, there is still room to manoeuvre in these relatively autonomous structures that are ultimately evaluated on their results (the annual production of a certain number of high-quality papers). On the other hand, ACS is seen as a vessel whose course cannot easily be deviated. The conclusion calls for extending this type of investigation to other contexts or types of journals.